Comparison study on rock breaking characteristics of disc cutters under coupled static–dynamic loads and static loads - Lin, Laikuang; Xia, Yimin; Zhang, Xuhui; Yi, Liang; Fu, Jie (Comptes Rendus. Mécanique)
Rock cutting methods for disc cutters with coupled static–dynamic loads and static loads are explored and compared through rock breaking experiments to improve the TBM excavation efficiency. Results indicate that the rock breaking characteristics, including rock debris, cutting force, and rock breaking efficiency, significantly varies with different cutting methods. The average size of rock fragmentation produced under coupled static–dynamic loads is 1.6 times larger than that under static loads. The cutting forces of disc cutter under the coupled static–dynamic loads are larger than those under static loads when the cutting depth $(h)$ is lower than 4 mm, whereas is contrary when $h$ exceeds 4 mm. The specific energy of disc cutter under the coupled static–dynamic load is approximately 1.5 times smaller than that under the static load, indicating the cutting method with the coupled static–dynamic load can significantly improve the cutting performance. There is an optimal cutter spacing $(S)$ for the cutter under each cutting method. The optimal $S$ under the coupled static–dynamic loads is larger than that with static loads. This study provides new insights into improving the tunneling efficiency in high-strength rock conditions.